2016
DOI: 10.1116/1.4941367
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and chemical changes of aerosolized E. coli treated with a dielectric barrier discharge

Abstract: This study presents the morphological and chemical modification of the cell structure of aerosolized Escherichia coli treated with a dielectric barrier discharge (DBD). Exposure to DBD results in severe oxidation of the bacteria, leading to the formation of hydroxyl groups and carbonyl groups and a significant reduction in amine functionalities and phosphate groups. Near edge x-ray absorption fine structure (NEXAFS) measurements confirm the presence of additional oxide bonds upon DBD treatment, suggesting oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…[ 8,17 ] However, the efficacy of treatments depends on genome structure of the pathogens and their replication machinery [ 18 ] ; furthermore, new technologies must take into account the possibility that both bacteria and viruses could develop harmful mutagenic outcomes associated with multiple transition mutations across the genome when they are underexposed or undergo insufficient inactivation treatments. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 8,17 ] However, the efficacy of treatments depends on genome structure of the pathogens and their replication machinery [ 18 ] ; furthermore, new technologies must take into account the possibility that both bacteria and viruses could develop harmful mutagenic outcomes associated with multiple transition mutations across the genome when they are underexposed or undergo insufficient inactivation treatments. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that a 1.5‐ and 5.5‐log reduction of the airborne Escherichia coli are achieved, respectively, after single plasma exposure of 10 s and 2 min. [ 19,28 ] Another study demonstrated that NTP generated by a wire‐to‐plate type DBD reactor induces a significant inactivation of both Bacillus subtilis ‐ and Pseudomonas fluorescens‐ containing bioaerosol. [ 2 ] Park et al [ 1 ] used a different kind of DBD architecture to effectively inactivate Staphylococcus epidermidis bioaerosols using a short residence time (0.24 s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a decrease in the peak intensity and slight shi towards the higher wavenumber in the region between 3700 and 3500 cm À1 , which could be assigned to the free -OH group. [49][50][51] Signicant disorder was observed in the 3000-2800 cm À1 region, demonstrating that fatty acids of various membrane components were reduced and transformed. 50 The peaks at 1645 and 1550 cm À1 due to the presence of amide I and amide II bands of proteins and peptides shied to the lower wavenumbers 1640 and 1548 cm À1 , respectively, indicating changes in the protein structures aer the treatment.…”
Section: Changes In the Bacterial Cells Aer The Photocatalytic Treatmentioning
confidence: 96%
“…Previous work using the DBD system was focused on Escherichia coli, a Gram-negative bacteria. 14 The distinctive difference between Gram-negative and Gram-positive bacteria is the presence of a thick peptidoglycan outer layer on Gram-positive bacteria whereas Gram-negative bacteria have a thin peptidoglycan structure. The mentioned study concluded that E. coli cell structure was damaged to varying extent and a severe oxidation of the cell membrane was found, establishing effective inactivation of the bacteria.…”
Section: Introductionmentioning
confidence: 99%